Weight loss as primary indication for FDG-PET/CT. Issue 10 (October 2020) - Maliha, Peter George; Singerman, Julia; Probst, Stephan
Abstract : Purpose: Some consider fluorodeoxyglucose positron emission tomography with computed tomography (FDG-PET/CT) clinically useful in patients presenting with nonspecific symptoms of malignancy, weight loss most commonly encountered. However, the appropriateness of such FDG-PET/CT studies remains to be clarified. This study evaluated the clinical value of FDG-PET/CT in patients referred primarily for weight loss. Methods: From 2010 to 2017 in one academic center, 252 subjects underwent 254 FDG-PET/CT studies for weight loss as primary indication and retrospectively studied. Eighteen subjects were excluded due to ongoing active malignancy, weight loss not ultimately being the main indication for the FDG-PET/CT, technically inadequate FDG-PET/CT and insufficient follow-up. The FDG-PET/CT scans were considered clinically beneficial when true positive for the cause of weight loss that other investigations missed or would have missed, clinically neutral when true negative and clinically detrimental when false positive leading to additional investigations or false negative. Results: Ultimately 234 unique subjects (236 FDG-PET/CT studies) were included. The average subject weight loss prior to the PET was 12 kg and average follow-up time post FDG-PET/CT scan was 3.4 years. The FDG-PET/CT scans were true positive in 24 studies (10%) with 8 studies (3%) clinically beneficial; false positive in 38 studies (16%) of which 26 led to 35 additional procedures and false negative in 13 studies (6%). In total, 39 (17%) FDG-PET/CT studies were clinically detrimental. The other 149 (63%) studies were true negative, clinically neutral. Conclusion: FDG-PET/CT appears to have limited value in assessing subjects with weight loss as the leading clinical indication, proving to be five times more often detrimental than beneficial.